2012
DOI: 10.1021/ac203152z
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity for Soot Sensing: Possibilities and Limitations

Abstract: In this study we summarize the possibilities and limitations of a conductometric measurement principle for soot sensing. The electrical conductivity of different carbon blacks (FW 200, lamp black 101, Printex 30, Printex U, Printex XE2, special black 4, and special black 6), spark discharge soot (GfG), and graphite powder was measured by a van der Pauw arrangement. Additionally the influence of inorganic admixtures on the conductivity of carbonaceous materials was proven to follow the percolation theory. Struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 59 publications
2
30
0
3
Order By: Relevance
“…The increase of conductivity from Flame 1 to Flame 4 sample follows the increase of I(D)/(IG) and can be therefore correlated to the increase of the in plane size of graphitic crystallites within the particles, L a , in agreement with the graphitization trajectory derived from Raman and optical band gap results. This trend is consistent to that observed by Grob et al [16], who measured the ratio of the two maxima in Raman the spectrum, I(D)/I(G), and the conductivity of a spark discharge generated soot and others disordered carbons, and observed that conductivity increased with I(D/I(G)). The same group also reported a larger amount of elemental carbon, and hence graphitization, in the samples with the larger conductivity [36].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The increase of conductivity from Flame 1 to Flame 4 sample follows the increase of I(D)/(IG) and can be therefore correlated to the increase of the in plane size of graphitic crystallites within the particles, L a , in agreement with the graphitization trajectory derived from Raman and optical band gap results. This trend is consistent to that observed by Grob et al [16], who measured the ratio of the two maxima in Raman the spectrum, I(D)/I(G), and the conductivity of a spark discharge generated soot and others disordered carbons, and observed that conductivity increased with I(D/I(G)). The same group also reported a larger amount of elemental carbon, and hence graphitization, in the samples with the larger conductivity [36].…”
Section: Resultssupporting
confidence: 92%
“…4 left side. Similar trends are reported in literature [16,36]. It is unlikely that such inverse trend is due to uncertainties in the determination of the G band by the fitting procedure.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These soot particles are composed of chain-like agglomerates of nearly spherical particles approximately 50 nm in diameter containing turbostratic graphite crystallites with an H/C ratio of approximately 0.01. These latter particles have a lower optical band gap than CNPs, fractions of eV, therefore absorbing light over a wide spectral range from the UV to IR and possessing a large electrical conductivity [23,24]. Therefore, it is evident that the particles produced in the various stages of the flame process have different electronic structures, characterized by the different positioning of the electronic bands, thus having different band gap values.…”
Section: Introductionmentioning
confidence: 99%
“…4 In-situ sensor technologies are typically based on either resistive techniques that detect soot accumulation [5][6][7] or electrostatic methods that determine real-time particle concentrations. 10,11 A recently developed, low-cost electrostatic in-situ PM measurement approach has demonstrated both higher sensitivity and better durability compared to resistive techniques.…”
mentioning
confidence: 99%